Development of an Infusion for Dysmenorrhea Based on Fig Leaves (Ficus Carica) and Mango - Revelo-Cáceres, Daniel; Oliveras-López, María Jesús; Serrana, Herminia López-García de la (European Journal of Applied Sciences, 2022)
An infusion based on fig leaves and mango was developed. Its sensory acceptability was evaluated as a possible alternative for the treatment of dysmenorrhea. Fig leaves and mangoes were washed, cut, dehydrated and ground. The optimal time for fig leaf dehydration was determined by means of a weight loss curve, producing an outcome of 120 minutes at 45ºC. Two formulations were made, the first containing 1 g of dehydrated fig leaves and 0.6 g of dehydrated mango, and the second containing 1 g of dehydrated fig leaves and 6 g of dehydrated mango. Sensory analysis was performed according to taste, aroma, paired preference and purchase intention ranking tests. Tasters preferred the formulation with the least amount of dried mango. 93% of tasters indicated that they would buy this infusion due to its possible functional properties against dysmenorrhea.